2010
DOI: 10.1111/j.1365-2648.2010.05277.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of respiratory‐sinus‐arrhythmia biofeedback on state‐anxiety in patients undergoing coronary angiography

Abstract: Psychological support including respiratory-sinus-arrhythmia biofeedback is an effective and simple tool that could be used by nurses to reduce state-anxiety and emotional stress in patients undergoing coronary angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 24 publications
1
33
0
5
Order By: Relevance
“…It was demonstrated that noninvasive methods such as CT virtual colonoscopy [15], MR cholangiopancreatography [16], and MR angiography of the carotid arteries [17] are more widely accepted by patients than the traditional invasive approaches [18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that noninvasive methods such as CT virtual colonoscopy [15], MR cholangiopancreatography [16], and MR angiography of the carotid arteries [17] are more widely accepted by patients than the traditional invasive approaches [18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the success of a method is undeniably associated with the intrinsic acceptance of the method by the patients, who are increasingly pursuing noninvasive and outpatient diagnostic examinations [14]. On the one hand, recent studies have shown that noninvasive tools such as CT virtual colonoscopy [15], magnetic resonance (MR) cholangiopancreatography [16], and MR angiography of the carotid arteries [17] are widely accepted by patients more than the traditional invasive approach, on the other hand it is known that conventional coronary angiography (CCA) may cause intense concern and anxiety in the patients and affect their quality of life especially in the hours before the examination, with the need for pharmacological and/or psychological treatment [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Muitas doenças foram foco de atenção dos estudos selecio-nados nesta revisão, dentre elas cefaleia em mulheres (17) e cefaleia em crianças (18) , síndrome do vômito cíclico em adolescente (19) , dispepsia funcional (20) , estresse pós-traumático (TEPT) (21) , angiografia coronariana (22) , manejo de estresse para enfermeiras (23) , dor no pescoço (24) , ansiedade entre estudantes de enfermagem (25)(26) , ansiedade e depressão em crianças (27) , doença coronariana (28) e dor oncológica (10) , além de um artigo de revisão (12) que analisou o emprego do biofeedback no tratamento de transtornos relacionados ao estresse e à ansiedade. Em relação aos participantes, os estudos foram realizados tanto com homens quanto com mulheres, o número de participantes foi entre um e 212 indivíduos e com grande variabilidade de idade, desde crianças (oito anos), adolescentes, adultos e idosos (80 anos).…”
Section: Bf De Variabilidade Cardíacaunclassified
“…Variáveis, como dor, qualidade de vida, grau de somatização, nível de satisfação e funcionamento psicossocial também foram avaliadas. Dentre os testes de ansiedade, os mais utilizados foram: inventário de ansiedade traço-estado (IDATE) em sete artigos (17)(18)(22)(23)(25)(26)(27) ; Multidimensional Anxiety Scale fo Children (MASC) (27) ; Hamilton Rate Scale for Anxiety (HAM-A) (17) ; Hospital Anxiety and Depression Scale (HAD) (24,28) , State-Trait Anxiety Inventory for Children (STAIC) (27) e Lasa Anxiety Scale (23) . Sintomas de estresse foram avaliados pelas escalas Stress Medicine Symptom Scale (SMSS) (24) , Perceived Stress Scale (PSS) e Post-traumatic Stress Disorder Checklist (PTSD) (21) .…”
Section: Bf De Variabilidade Cardíacaunclassified
See 1 more Smart Citation